Speleonectes cokei, new species of Remipedia (Crustacea: Speleonectidae) from a submerged ocean cave near Caye Chapel, Belize - Yager, Jill (Zootaxa, 2013)
Speleonectes cokei n. sp. is the 15th species of Speleonectes to be described. It is the first remipede described from a submerged cave off the mainland of Belize. The species is the third found along the Caribbean coast of the Yucatan Peninsula. S. cokei can be distinguished from S. tulumensis Yager, 1987 and S. fuchscockburni Neiber et al., 2012 by the number of antenna 1 segments, number of antenna 2 exopod setae, spines on maxilla 1 segment 2, and caudal rami to anal segment length.